A Screening Procedure for Evaluating Cotton for Rotylenchulus reniformis Resistance in Controlled Conditions - Konan, NO.; De Proft, M.; Ruano, O.; Baudoin, JP.; Mergeai, G. (Tropicultura, 2014)
Rotylenchulus reniformis is one of the most important nematode pests of cotton. Currently, no cotton cultivar resistant cotton cultivar to this pest is available. In the framework of a breeding program aiming at producing cotton genotype resistant to this nematode, a R. reniformis resistance evaluation protocol based on egg inoculation, extraction and counting, has been established. Two environment conditions (growth chamber and greenhouse), four sieves (75, 50, 20 and 10 µm), three doses of inoculum (1,500; 3,000 and 6,000 eggs), and five durations of infestation (20, 30, 40, 50 and 60 days after inoculation) have been tested. The growth chamber programmed to provide 12 h of light, 55%-60% relative humidity and 30-26°C day-night air temperatures revealed to be adequate. The NaOCl (sodium hypochloride)-blender-sieving-centrifugation-flotation method, using 75-µm and 20-µm sieves, kaolin powder and MgSO4 (magnesium sulfate) solution (specific gravity 1.18) proved to be suitable for effective R. reniformis egg extraction (from roots) and counting. Inoculation of 6,000 eggs per seedling and 60 days duration of infestation seemed to be sufficient dose and period for a reliable resistance evaluation. The protocol developed has been tested on known susceptible and resistant cotton genotypes: G. hirsutum L (main cultivated species through the world, susceptible), G. thurberi Tod. (wild cotton species, moderately susceptible) G. longicalyx Hutch. and Lee (wild cotton species, very resistant). The results obtained were in accordance with the response expected from the genotypes tested, proving the reliability of the evaluation procedure developed.